2022
DOI: 10.1002/lsm.23546
|View full text |Cite
|
Sign up to set email alerts
|

Skin of color representation in cosmetic clinical trials: A literature review

Abstract: Despite cosmetic procedures being on the rise in the US in all demographics, cosmetic procedures remain heavily skewed towards non-skin of color patients. Cosmetic clinical trials in the United States must be representative of the everincreasing diversity of the US population. We sought to analyze published cosmetic randomized controlled trials, both industry-sponsored and investigatorinitiated, to characterize and assess representation of skin of color participants over the past three decades. Our study shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
(14 reference statements)
3
9
0
Order By: Relevance
“…As a majority of laser and energy‐based devices are for skin usage, thus it is especially important to have representation from different race and ethnicities given the increasing diverse demographics of the patient population and need to reduce existing health disparities. Recent studies have demonstrated that cosmetic procedures are heavily geared toward non‐skin of color patients 6 and the poor study participant ethnic/racial diversity in aesthetic trials 7 …”
Section: Discussionmentioning
confidence: 99%
“…As a majority of laser and energy‐based devices are for skin usage, thus it is especially important to have representation from different race and ethnicities given the increasing diverse demographics of the patient population and need to reduce existing health disparities. Recent studies have demonstrated that cosmetic procedures are heavily geared toward non‐skin of color patients 6 and the poor study participant ethnic/racial diversity in aesthetic trials 7 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indirectly addressed the degree of laser training in the dermatology residency, but current information regarding safety education, frequency of procedures, industry relations, and laser career plans of dermatology residents is incomplete. [1][2][3][4] This study aimed to characterize cosmetic laser education and assess perceived competency and future practice plans among dermatology residents.…”
mentioning
confidence: 99%
“…There have been extraordinary advancements in the use of laser treatments for dermatologic conditions. 1,2 However, inclusion of participants with skin of color (SOC) in laser-based clinical trials is largely understudied. 2 When included, SOC is often defined through self-reported measures of race and/or ethnicity that have often been shown to be nonspecific and inacurrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Within cosmetic dermatology, these disparities have been documented in both clinical trials and advertisements. 2,3 Cosmetic grading scales serve as the objective foundational framework for critically assessing treatment results. Given the racial and ethnic differences in skin characteristics, it is important to have appropriate representation in cosmetic grading scales to perform high quality, inclusive, and generalizable research.…”
mentioning
confidence: 99%